The use of questioning techniques as a strategy to enhanve students' responses during english language lessons - Tan, Yee Suan (Universiti Malaysia Sarawak, UNIMAS, 2009)
The present study examines the use of questioning techniques as a strategy to enhance students’ responses during English language lessons. It is devised specifically to answer five research objectives, that is to ‘determine the average number of questions asked by teachers’, ‘identify the types of questions used by teachers’, ‘identify the questioning techniques used by teachers’, ‘identify whether teachers’ questioning techniques vary with students of different proficiency levels’ and ‘analyse whether teachers’ questioning techniques help in building students’ responses during an English language lesson’. This qualitative study adopted the case study format that employed two instruments, namely observation notes and a tape recorder. The sample respondents were taken from five classes of Form Two students as well as their English language teachers. Fifteen observations of classroom proceedings were audio-recorded for a period of three weeks. Observation notes that focused on teachers’ questions and students’ responses in a classroom discourse were written down to ensure the accuracy of the data. The recorded conversations were played numerous times to double check the reliability of the observation notes. After that, the data collected were further compiled, analyzed, tabulated and explained with reference to the research questions mentioned in this study. The findings of the study revealed that the average number of questions asked per lesson was pitched at thirty-five questions in a forty minutes lesson. Besides, the findings also implied that both teachers had directed numerous questions towards their students. However, most of the questions asked were display questions, which mean to elicit factual information. Moreover, the study also indicated that questioning techniques such as prompting, probing, redirecting and rephrasing questions were able to encourage students to respond actively in class despite the fact that rephrasing question was the only questioning technique employed in the four lessons observed. Furthermore, the study also signified that teachers used different types of questions to deal with students of different abilities. Here, there is likelihood for the teacher to pose more referential and probing questions to the advanced students. As for the weaker students, they were posed with more display and prompting questions. Also, it was concluded that not all questioning techniques were able to build up students’ responses in class. In fact, referential, prompting, probing, rephrasing and redirecting questions were the only questioning techniques that help the students to build their responses in class to a certain extent. Further explanation on the results can be found in the report.